Primary Effect of SERCA2a Gene Transfer on Conduction Reserve in Chronic Myocardial Infarction. Issue 18 (18th September 2018) - Motloch, Lukas J.; Cacheux, Marine; Ishikawa, Kiyotake; Xie, Chaoqin; Hu, Jun; Aguero, Jaume; Fish, Kenneth M.; Hajjar, Roger J.; Akar, Fadi G.
Abstract : Background: SERCA2a gene transfer (GT) improves mechano‐electrical function in animal models of nonischemic heart failure Whether SERCA2a GT reverses pre‐established remodeling at an advanced stage of ischemic heart failure is unclear. We sought to uncover the electrophysiological effects of adeno‐associated virus serotype 1.SERCA2a GT following myocardial infarction (MI). Methods and Results: Pigs developed mechanical dysfunction 1 month after anterior MI, at which point they received intracoronary adeno‐associated virus serotype 1.SERCA2a (MI+SERCA2a) or saline (MI) and were maintained for 2 months. Age‐matched naive pigs served as controls (Control). In vivo ECG‐and‐hemodynamic properties were assessed before and after dobutamine stress. The electrophysiological substrate was measured using optical action potential (AP) mapping in controls, MI, and MI+SERCA2a preparations. In vivo ECG measurements revealed comparable QT durations between groups. In contrast, prolonged QRS duration and increased frequency of R′ waves were present in MI but not MI+SERCA2a pigs relative to controls. SERCA2a GT reduced in in vivo arrhythmias in response to dobutamine. Ex vivo preparations from MI but not MI+SERCA2a or control pigs were prone to pacing‐induced ventricular tachycardia and fibrillation. Underlying these arrhythmias was pronounced conduction velocity slowing in MI versus MI+SERCA2a at elevated rates leading to ventricular tachycardia and fibrillation. Reduced susceptibility to ventricular tachycardia and fibrillation in MI+SERCA2a pigs was not related to hemodynamic function, contractile reserve, fibrosis, or the expression of Cx43 and Nav1.5. Rather, SERCA2a GT decreased phosphoactive CAMKII‐delta levels by >50%, leading to improved excitability at fast rates. Conclusions: SERCA2a GT increases conduction velocity reserve, likely by preventing CAMKII overactivation. Our findings suggest a primary effect of SERCA2a GT on myocardial excitability, independent of altered mechanical function.